THE INFLUENCE OF E-SERVICE QUALITY ON USER SATISFACTION OF THE THREADS APPLICATION AMONG STUDENTS OF THE FACULTY OF SOCIAL AND POLITICAL SCIENCES - Cut Sukmawati; Khairani; Nanda Ameliany; Maisyura; Nursakinah Ritonga (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
E-Service Quality is one of the important variables in shaping user satisfaction on social media, such as the Threads application. The purpose of this study is to examine the effect of E-Service Quality on User Satisfaction of the Threads Application among students of the Faculty of Social and Political Sciences, Malikussaleh University. This study uses a quantitative method with an associative research type. The research sample used in this study was 100 respondents selected using a non-probability purposive sampling technique. The collected data were analyzed using a simple linear regression test. Based on the results of the analysis, it is shown that E-Service Quality has a positive and significant influence on User Satisfaction of the Threads application with a t-value of 9.848 greater than the t-table of 1.98447 and a significance value of 0.000 <0.05, so H1 is accepted. The coefficient of determination (R²) of 0.497 means that E-Service Quality significantly influences user satisfaction by 49.7%, while 50.3% is influenced by other factors outside the research variables.